Next generation crosscutting themes: Factors that contribute to students' understandings of size and scale. Issue 6 (18th February 2018) - Chesnutt, Katherine; Jones, Melissa Gail; Hite, Rebecca; Cayton, Emily; Ennes, Megan; Corin, Elysa N.; Childers, Gina
Abstract: This study examined the degree to which individual differences in students' ( N = 232) concepts of size and scale are explained by factors such as students' innate sense of number, out‐of‐school science experiences, exposure to size and scale instruction, gender identities, and racial/ethnic identities. There is increasing emphasis being placed on the use of crosscutting concepts to promote deep learning in science. A multiple linear regression indicated students' racial/ethnic identities, experiences with scale outside of school, and exposure to size and scale instruction significantly added to the prediction model. Results from this study can both inform the movement toward incorporating crosscutting concepts into pedagogy as well as inform educators, administrators, and other stakeholders of the factors that may shape students' understanding of the cross‐cutting concept of scale, proportion, and quantity.